Coinvolgere i genitori nella scuola multiculturale. Un progetto di ricerca azione per la costruzione di una cultura della partecipazione - Bolognesi, Ivana (Rivista Italiana di Educazione Familiare, 2016)
This essay describes an action research realized with a group of italian schools with many migrant children. This project - which is part of the European project "Empae" (Engaging Migrant Parents and Children) - is aimed at promoting school success the school success of children with migrant backgrounds through the construction of a working model based on the involvement of families and on the development of training activities for teachers. In particular, the following actions were been activated: to promote actions addressed to immigrant families, to increase their expectations on the children’s schooling processes. The research team was be composed by researchers and teachers, and all the actions were been realized through observations, interviews and focus groups.